Une administration sans domination ? Le projet constitutionnel de 1790 ou l’éphémère « modernisation » démocratique de l’administration territoriale (1789-1793) - Gaïd Andro (Mélanges de la Casa de Velázquez)
The history of the French state has long been overwhelmed by a teleological vision initiated by nineteenth-century liberal writers and emphasizing the long centralizing continuum between monarchic absolutism, “Jacobin” centralization, the Empire and the succession of nineteenth-century political regimes. Following this logic, territorial administration, studied both by historiography and by theorists of classical law, was a fundamental instrument in the long “conquest” of the centre over its peripheries. As an organ of political power, local administration would have had the role of executor and relay between the central power and the provinces/departments, reflecting the binary nature of a pyramidal link composed of subordination and/or contestation. Thus, the modernisation of the state and the growth of the administrative bureaucracy were linked in a joint quest for efficiency and rationality. However, the administrative project of the revolutionaries of 1789, in other words their political conception of the territory, reflects an entirely different logic. Indeed, insofar as the law was envisaged by the first Constituents as the perfect translation of the general will resulting from the sovereignty of the people, its execution was theoretically based on popular consent, which could not be a constraint, even if negotiated. In short, the constitutional project of the early Revolution can be seen as an alternative to the modernising vulgate of the 19th century and as an original political thought that renews the link between sovereignty and territory through the regeneration of the territorial executive power thought as the implementation of political freedom.